Degradation Behaviour of Deteriorated RC Beams Strengthened with CFRP under the Compound Effects of Acid-Salt Mist and Carbon Dioxide - Wei Wang; Yuan-zhou Wu; Zhongnian Fang (Advances in Civil Engineering)
The reinforcement effect and durability of carbon fibre-reinforced polymer (CFRP) sheets are important indicators that affect its promotion and application. This study conducted an experimental investigation of the degradation behavior of reinforced concrete (RC) beams strengthened with CFRP. The RC beams were deteriorated under the compound effects of acid-salt mist and carbon dioxide for a time period t1i, then strengthened with one or two layers of CFRP sheets, and placed in the same deterioration environment for an additional time period t2i. The failure modes, load-deflection curves, rigidity, and flexural carrying capacity changes were studied after the deteriorated RC beams were loaded to failure. Three combinations of deterioration periods were considered in this study: different t1i and same t2i, same t1i and different t2i, and same total time (t1i + t2i). This study found that the U-shaped hoops and the side concrete peeled off gradually as the CFRP-strengthened RC beams were deteriorated again with time. Under the ultimate load, the strengthening layer in the tension zone stripped. The strengthened layer, which consisted of CFRP, a binder, and the concrete cover, was stripped from the RC beam during loading. The deflection of the strengthened layer behaved differently from the other part; this disharmony prevented the mobilization of the tensile advantage of CFRP. The mechanism of RC beam’s mechanical behaviour was analyzed in terms of the degrees of deterioration of RC beams and CFRP and their coupled effects. The conclusions of this study can be used as references in the prediction of strength changing and service life of strengthened RC beams.